Effect of banana skins filler on thermal behavior of natural rubber latex films - Low, Miao Ying (2012)
This study is done to produce latex film with 0 %, 5 %, 10 %, 15 % and 20 % banana skins as filler and to investigate the effect of banana skin on thermal behavior of natural rubber latex films. Banana skin contains a lot of minerals, sugar, starch, protein and so on. The bio-based material such as starch is widely use in latex industries to produce of biodegradable plastic and in the production of latex glove due to its properties. In terms of industrial application, thermal performance of rubber is the key importance since in the production of rubber based products processing temperature are usually high and close to their degradation temperature. Banana skin is dried by using drying cabinet at 40 °C until fully dried and followed by grinding process by using grinder to get banana skin powder. Sieving process is necessary to produce fine banana skin powder before dissolve it into distilled water. Effect of different banana loading on natural rubber latex films are investigated after vulcanization process and dipping process. Thermal properties of the natural rubber latex which filled with banana skin powder are determined by using Mettler Toledo Thermagravimetric Analyzer/Differential Scanning Calorimeter (TGA/DSC). It can evaluate the thermal stability such as weight loss, rate of degradation and also heat flow. Finally, observation for microscopic behavior on surface of films will carry out by using Scanning Electron Microscope (SEM). This is to study the dispersion of different banana loading on the natural rubber latex films. There are no significant difference in term of thermal stability of pure natural rubber latex film and natural rubber latex with filler. Therefore by adding banana skin powder into natural rubber latex is potentially to apply in latex based product industry.